Perancangan Sistem Ulangan Harian Online Berbasis Whatsapp Auto Respon di SMK N 1 Rao Selatan - Saputri, Nefri; Okra, Riri; Musril, Hari Antoni; Khairuddin, Khairuddin (Indonesian Research Journal on Education, 2022)
Daily tests are part of the evaluation system carried out by educators to students to measure and assess the achievement of student competencies after completing basic competencies (KD) in learning. In this school, the daily test process is manual or conventional, where the daily test is done by doubling the questions, using paper, stationery and the results of the daily tests are checked by writing on paper one by one. Of course it has drawbacks, namely increasing answer sheets, requiring paper costs, teachers calculating relatively long scores and the time it takes students to find out values is relatively long. This type of research uses Research and Development research with the abbreviation (R&D) with a 4D version development model (Four D) with the stages ofdefine, design, develop and desiminate. As well as the development model using the SDLC (SystemDevelopment Life Cycle) with the Waterfall model with the stages of communication, planning,modeling, construction, and deployment. The results of this product test have been carried out with several lecturers (computer and education experts), teachers, and students. With the Validity Test with expert lecturers in the field of computers and education obtaining 0.72, it is categorized asvalid, the Practicality Test conducted by the teacher obtains 0.84 which is declared high and the value of the Effectiveness Test tested on students is 0.79 declared effective.